Enhancing early psychosis treatment using smartphone technology: A longitudinal feasibility and validity study. (January 2018) - Niendam, Tara A.; Tully, Laura M.; Iosif, Ana-Maria; Kumar, Divya; Nye, Kathleen E.; Denton, Jennifer C.; Zakskorn, Lauren N.; Fedechko, Taylor L.; Pierce, Katherine M.
Abstract: Smartphone applications that promote symptom tracking and self-management may improve treatment of serious mental illness (SMI). Although feasibility has been established in chronic adult outpatient or inpatient SMI samples, no data exist regarding implementation of smartphone technology in adolescent and young adult populations as part of early psychosis (EP) outpatient care. We implemented a smartphone "app" plus clinician Dashboard as an add-on treatment tool in the University of California, Davis Early Psychosis Program. Participants completed daily and weekly surveys examining mood, symptoms, and treatment relevant factors via the app for up to 14 months. Clinicians discussed symptom ratings and surveys during regular treatment sessions using the Dashboard. We report methodological details of the study, feasibility metrics, and analyses of the validity of measuring symptoms via self-report using mobile health (mHealth) technology in comparison to gold-standard clinician-rated interviews based on a comprehensive longitudinal analysis of within-person data. Results demonstrate that integrating mHealth technology into EP care is feasible and self-report assessment of symptoms via smartphone provides symptom data comparable to that obtained via gold-standard clinician-rated assessments.